An economic analysis of sweet potato production and utilization for animal feed on North Vietnam - Nguyen, T.S. (University of the Philippines, 1997)
The study aimed to determine the effects of government policies on the incentive structure of the sweet potato industry. It reviewed the national program on sweet potato production and the government policies in the input and output markets of the sweet potato industry and related these to the question of whether or not the country has comparative advantage in sweet potato production. The nominal protection rate (NPR) was used as measure of production incentive. On the other hand, the comparative advantage study focused on the concept of net social profitability (NSP). Results showed that government policies provided incentives to sweet potato growers, as indicated by the NPR values which ranged from 7 - 25 percent. However, these also served as disincentives for sweet potato growers by imposing positive implicit tariff (IT) on major inputs (e.g., fertilizer) used for sweet potato production. The NSP values in all study areas were positive, showing that sweet potato production in North Vietnam had comparative advantage, or sweet potato production in the study areas used domestic resources more efficiently. The largest NSP value was three thousand five hundred seventeen point five dong and the smallest value was one hundred eight-two dong per hectare of sweet potato in Hatay and Hanoi, respectively. The study also evaluated the prospects of using sweet potato products (roots and vines) were mainly used for swine feed. The largest proportion of roots used as feed was 82.1 percent and the smallest was 50.2 percent in Hatay and Thanhhoa, respectively. For sweet potato vine, the highest proportion used was 80.8 percent in Thanhhoa and the lowest was 54.5 percent in Hanoi. Sweet potato occupied a large part in total feeds costs for swine: 16.5 - 33.6 percent in Bacthai and 29.1 - 45.1 percent in Thanhhoa. Weight gains of swine fed with sweet potato, which has good supplemental protein, was at par with those given commercial feeds. The study showed that using sweet potato as the main feed ingredient for swine.